Grotesque and caricature : Leonardo to Bernini - Norris, Rebecca; Norris, Rebecca; Tantardini, Lucia; Tantardini, Lucia (Brill's studies on art, art history, and intellectual history, 2024)
"Grotesque and Caricature: Leonardo to Bernini examines these two genres across Renaissance and Early Modern Italy. Although their origins stem from Antiquity, it was Leonardo da Vinci's early teste caricate that injected fresh life into the tradition, greatly inspiring generations of artists. Critical among them were his Milanese followers, such as Giovanni Paolo Lomazzo, and also Michelangelo and Sebastiano del Piombo as well as, notably, Annibale Carracci, Guercino, and Bernini among others. Their artistic production-drawings, prints, paintings, and sculpture-reveals deep interest in physical, physiognomic, and psychological observations with a penchant for humour and wit. Written by an international group of established and emerging scholars, this volume explores new insights to these complementary artistic genres. Contributors include: Carlo Avilio, Ilaria Bernocchi, Christophe Brouard, Sandra Cheng, Susan Klaiber, Michael W. Kwakkelstein, Tod A. Marder, Rebecca Norris, Lucia Tantardini, Nicholas J. L. Turner, Mary Vaccaro, and Matthias Wivel"--